MAJALAH SEBAGAI MEDIA DAKWAH - Ria Warda (AL TAJDID, 2009)
Along with current of growth of information media which is fast progressively, forms of forwarding of message whereabout activity da’wah the inclusive of in it, need to modernize according to growth of epoch and progress in civilization area. All of preacher (da’i) as well as target da’wah (mad’u) claimed to be able to exploit the media to quicken reaching of target da’wah. And one of among mission media which very require to be managed professionally to quicken reaching of da’wah target, is da’wah magazine. To reach the da’wah target which da’wah magazine circulating, hence very need the artistic values exploiting as a mean to generate the awareness that Allah swt. The most Respect and very loving beauty. But the beauty may not go out from corridor of statement of slave to Allah swt accompanied by the full of awareness that its slave status must continue at effort realize the function of human being as khalifatullah fil-Ardh (proxy of Allah swt and at one blow as the authorized one of power from Its in the world) to be prosperous of human life.